Proteolysis-targeting chimeras (PROTACs): a review of their development and potential pharmacological applications - Chfat, Karrar Najeh; Abdul Hussein, Shaker Awad (Pharmakeftiki, 2025)
Beyond conventional small-molecule inhibitors, proteolysis-targeting chimeras (PROTACs) represent a novel therapeutic strategy for targeted protein degradation. These heterobifunctional molecules are engineered in order to recruit an E3 ubiquitin ligase to a specific protein of interest, thereby facilitating its ubiquitination and subsequent degradation by the proteasome. This approach has garnered significant attention due to its ability to target proteins traditionally considered “undruggable”, including those lacking enzymatic activity or accessible binding pockets. This mini-review outlines the mechanistic basis of PROTACs, key design principles, and recent advances in the field. Particular emphasis is placed on the potential of PROTACs to address persistent challenges in drug discovery, notably the need for selective elimination of pathogenic proteins. The review also explores strategies for optimizing PROTAC-based therapies and discusses current limitations, such as pharmacokinetic constraints and the need for improved E3 ligase engagement. Owing to their distinctive mode of action and expanding therapeutic scope, PROTACs hold promise for transforming the treatment landscape of cancer, neurological disorders, and other diseases driven by aberrant protein expression.